Characterization of pseudoprogression in patients with glioblastoma: is histology the gold standard? - Melguizo-Gavilanes, Isaac (J Neurooncol, 2015)
Pseudoprogression (psPD) refers to an increase in size or appearance of new areas of MRI contrast enhancement soon after completing chemoradiation, timely diagnosis of which has been a challenge. Given that tissue sampling of the MRI changes would be expected to accurately distinguish psPD from true progression when MRI changes are first seen, we examined the utility of surgery in diagnosing psPD and influencing patient outcome. We retrospectively reviewed data from adults with GBM who had MRI changes suggestive of progression within 3 months of chemoRT; of these, 34 underwent surgical resection. Three subsets–tumor, psPD or mixed-were identified based on histology and immunohistochemistry in the surgical group and by imaging characteristics in the nonsurgical group. A cohort of patients with stable disease post-chemoRT served as control. PFS and OS were determined using the Kaplan–Meier method and log rank analysis. Concordance for psPD between radiological interpretation and subsequent histological diagnosis was seen in only 32 % of cases (11/34) 95 %CI 19–49 %. A large proportion of patients had a histologically “mixed” pattern with tumor and treatment effect. No significant differences in PFS or OS were seen among the three subtypes. Surgical sampling and histologic review of MRI changes after chemoRT may not serve as a gold standard to distinguish psPD from true progression in GBM patients. Refinement of the histological criteria, careful intraoperative selection of regions of interest and advanced imaging modalities are needed for early differentiation of PsPD from progression to guide clinical management.